DNA damage responses in Drosophila nbs mutants with reduced or altered NBS function. - Mukherjee, S.; LaFave, M.C.; Sekelsky, J. (DNA Repair, 2009)
The MRN complex, composed of MRE11, RAD50 and NBS, plays important roles in responding to DNA double-strand breaks (DSBs). In metazoans, functional studies of genes encoding these proteins have been challenging because complete loss-of-function mutations are lethal at the organismal level and because NBS has multiple functions in DNA damage responses. To study functions of Drosophila NBS in DNA damage responses, we used a separation-of-function mutation that causes loss of the forkhead-associated (FHA) domain. Loss of the FHA domain resulted in hypersensitivity to ionizing radiation and defects in gap repair by homologous recombination, but had only a small effect on the DNA damage checkpoint response and did not impair DSB repair by end joining. We also found that heterozygosity for an nbs null mutation caused reduced gap repair and loss of the checkpoint response to low-dose irradiation. These findings shed light on possible sources of the cancer predisposition found in human carriers of NBN mutations.